EFFICACY OF NON-PHARMACOLOGICAL APPROACHES TO IMPROVE SLEEP QUALITY INDICES IN POST-STROKE INSOMNIA PATIENTS - Hidayat, Shaffana; Veronica, Fifi; Amalia, Lisda; Goenawan, Hanna (MNJ (Malang Neurology Journal), 2024)
Background: Post-stroke insomnia (PSI) is a highly prevalent complication of stroke. Clinical manifestations of PSI include non-refreshing, non-restorative sleep quality and short sleep duration, leading to stroke recovery impediment, cognitive, emotional, and daytime dysfunction, and poor quality of life in stroke patients. PSI can be treated with medications, but studies have reported various adverse effects of hypnotic drugs in PSI. Objective: This study explores non-pharmacological treatments for their efficacy to improve sleep quality in PSI patients. Methods: An electronic search in Medline, Google Scholar, Elsevier, Directory of Open Access Journals (DOAJ), and Semantic Scholar was performed to identify studies examining the efficacy of non-pharmacological approaches to PSI. Results: A total of ten studies examining the efficacy of non-pharmacological approaches to PSI were reviewed. The characteristics of PSI patients in these studies comprised the older population typically at several months after suffering commonly from ischemic type stroke. The evaluated treatments are EEG biofeedback, acupuncture, cognitive-behavioral therapy (CBT), light therapy, and repeated transcranial magnetic stimulation (rTMS). All treatments successfully improved sleep quality, insomnia symptoms, and quality of life in stroke patients as assessed by various measurements including PSQI and actigraphy. Only mild adverse events were reported following acupuncture, such as local hematoma and hand numbness. Conclusion: Non-pharmacological approaches can be considered efficacious in improving sleep quality index, insomnia symptoms, and quality of life of PSI patients. Furthermore, they do not cause severe or long-lasting adverse effects, thus deemed safe for stroke patients.